Low-potential driven fully-depleted BiVO4/ZnO heterojunction nanodendrite array photoanodes for photoelectrochemical water splitting. (February 2017) - Yang, Jih-Sheng; Wu, Jih-Jen
Abstract: To enhance photoelectrochemical water splitting performance of the intrinsic BiVO4, a low-potential driven fully-depleted intrinsic BiVO4 -based photoanode is realized in this work by the conformal formation of thin BiVO4 layers (<15 nm) on the 3-μm-thick ZnO nanodendrite (ND) array followed by the deposition of co-catalyst cobalt phosphate (Co-Pi). The Co-Pi/BiVO4 /ZnO ND photoanode is fully-depleted at 0.8 V vs. the reversible hydrogen electrode (RHE) by the electric fields developed in radial directions of the nanorods and branches. Driven by the electric fields, the photogenerated electron-hole pairs in the whole electrode are efficiently separated and then the holes swiftly drift to the photoanode/electrolyte interface for oxygen evolution. Rather than diffusion, charge transport mechanism is governed by drift in the fully-depleted ND heterojunction array photoanode. As a result, in the high-light-harvesting BiVO4 /ZnO ND array photoanode, the obstacle of slow charge transport in BiVO4 can be surmounted due to the construction of the light absorption and hole drifting paths in different directions. The photocurrent density of the Co-Pi/BiVO4 /ZnO ND photoanode is optimized to be 3.5 mA cm −2 at 1.23 V vs. RHE. Graphical abstract: Low-potential driven fully-depleted BiVO4 /ZnO heterojunction nanodendrite array photoanodes is fabricated for photoelectrochemical water splitting. The electric field developed in radial directions of the nanorods and branches can drive efficient charge separation in the whole electrode. The holes drift following the electric fields with different directions from the light absorption path to the surface for further oxygen evolution. Rather than diffusion, charge transport mechanism is governed by drift in the fully-depleted ND heterojunction array photoanode. Highlights: BiVO4 /ZnO heterojunction nanodendrite array is fabricated for PEC water oxidation. It is fully-depleted at low enough potential by electric fields in radial directions. Photogenerated electron-hole pairs in the whole electrode are efficiently separated. Charge transport mechanism is governed by drift in the fully-depleted photoanode. Directions of hole drift and light harvesting are different in the photoanode.